2019
DOI: 10.1177/0890334419830992
|View full text |Cite
|
Sign up to set email alerts
|

Queering Lactation: Contributions of Queer Theory to Lactation Support for LGBTQIA2S+ Individuals and Families

Abstract: In this article I explore some contributions of queer theory to the provision of lactation support services. In doing so, I also undertake an intersectional analysis of queering lactation, recognizing that forms of oppression do not impact all individuals equally or in the same ways. While recognizing the history of tensions between queer and feminist politics and activism, I argue that queering lactation holds significant benefits for supporting lactation among LGBT families, as well as opening up possibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 38 publications
0
11
0
18
Order By: Relevance
“…Unfortunately, there is currently a considerable lack of research about factors influencing lactation among transgender men. The lack of evidence-based recommendations, gaps in clinician knowledge and experience, and the history of discrimination and macroaggressions against transgender patients in medicine all contribute to the ongoing medical disparities suffered by this at-risk population (Dodgson, 2019; Ferri et al, 2020; Lee, 2019; McDonald, 2019). This study is a first step in building an evidence-base about gender-affirming testosterone therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is currently a considerable lack of research about factors influencing lactation among transgender men. The lack of evidence-based recommendations, gaps in clinician knowledge and experience, and the history of discrimination and macroaggressions against transgender patients in medicine all contribute to the ongoing medical disparities suffered by this at-risk population (Dodgson, 2019; Ferri et al, 2020; Lee, 2019; McDonald, 2019). This study is a first step in building an evidence-base about gender-affirming testosterone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Transgender and gender diverse people experience considerable health care disparities from avoidance of medical care due to a history of mistreatment. Furthermore, health care professionals often lack clinical experience and there is a significant lack of research to guide evidence-based practices among transgender and gender diverse people (Dodgson, 2019; Ellis et al, 2015; Ferri et al, 2020; Lee, 2019). To date, our review of the literature identified only a single case report of a lactating transgender man who initiated testosterone therapy at 21 months postpartum and continued to provide human milk to his child while on testosterone therapy for an additional 15 months (McDonald et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finalement, l'ensemble des recherches recensées ainsi que l'échantillon de l'étude ne présentaient que des couples hétérosexuels. À cet effet, Lee [48] soulève l'importance d'apporter une sensibilité aux communautés LGBTQ+ dans les études portant sur l'allaitement.…”
Section: Discussionunclassified
“…It also spoke to the immense need there is in the lactation field for equity and inclusion in the provision of services and for research about how to resolve these disparities. The current JHL issue addresses a specific population -gender non-conformists -that often has been neglected in discussions of social justice (Lee, 2019). Although strides toward equity are being made every day, collectively and worldwide, we have not yet done the best we can to educate, facilitate, and support all breastfeeding/chestfeeding families, as the authors of articles for this special topic explain.Many of these inequities are surrounded by providers' lack of experience and/or knowledge base about the gender non-conforming population.…”
mentioning
confidence: 99%
“…Let us lead the way within the healthcare system toward more inclusive and compassionate practices for these families. Robyn Lee (2019) Breastfeeding chestfeeding, gender non-conforming, lactation, LGBTQI+, transgender, queer theory using a theoretical lens that positions lactation within gender non-conforming families as a social justice issue. Please use these seminal articles to inform your work in making the changes that must occur in both clinical care and research.…”
mentioning
confidence: 99%